Model Pergerakan Tumpahan Minyak di Perairan Selat Sunda dengan Gnome Analysis - Agus Salim; Taufik Edi Sutanto (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
Sunda Strait is an area of strait that has potential for enormous natural wealth. However, this potential is threatened by oil spills that occurred due to the activities of transportation and storage of crude oil. A study of ecological risk assessment of oil spills was conducted to measure the magnitude of the threat of oil spills and to have preemptive strategies to minimize the impact if a large-scale oil spills occur in the future. From the analysis of the trajectory, it can be concluded that the areas that are vulnerable to the impact of the oil spill were Panimbang Beach, Wells Island, Coastal Cigeulis, Cimanggu, Selat Panaitan, Cilegon, Anyer, Mediation, and Jabung Sragi. The applicability of the trajectory final data can be used as a reference in determining the risk level of oil particles which expose to ecosystems around the Sunda Strait and the foremost result was that it would be used to minimize the impact of the oil spills in the future.